Improvement of the Uranium Sequestration Ability of a Chlamydomonas sp. (ChlSP Strain) Isolated From Extreme Uranium Mine Tailings Through Selection for Potential Bioremediation Application - Baselga-Cervera, Beatriz; Romero-López, Julia; García-Balboa, Camino; Costas, Eduardo; López-Rodas, Victoria (Frontiers in Microbiology, 2018)
The extraction and processing of uranium (U) have polluted large areas worldwide, rendering anthropogenic extreme environments inhospitable to most species. Noticeably, these sites are of great interest for taxonomical and applied bioprospection of extremotolerant species successfully adapted to U tailings contamination. As an example, in this work we have studied a microalgae species that inhabits extreme U tailings ponds at the Saelices mining site (Salamanca, Spain), characterized as acidic (pH between 3 and 4), radioactive (around 4 μSv h−1) and contaminated with metals, mainly U (from 25 to 48 mg L−1) and zinc (from 17 to 87 mg L−1). After isolation of the extremotolerant ChlSP strain, morphological characterization and internal transcribed spacer (ITS)-5.8S gene sequences placed it in the Chlamydomonadaceae, but BLAST analyses identity values, against the nucleotide datasets at the NCBI database, were very low (<92%). We subjected the ChlSP strain to an artificial selection protocol to increase the U uptake and investigated its response to selection. The ancestral strain ChlSP showed a U-uptake capacity of ≈4.30 mg U g−1 of dry biomass (DB). However, the artificially selected strain ChlSG was able to take up a total of ≈6.34 mg U g−1 DB, close to the theoretical maximum response (≈7.9 mg U g−1 DB). The selected ChlSG strain showed two possible U-uptake mechanisms: the greatest proportion by biosorption onto cell walls (ca. 90%), and only a very small quantity, ~0.46 mg g−1 DB, irreversibly bound by bioaccumulation. Additionally, the kinetics of the U-uptake process were characterized during a microalgae growth curve; ChlSG cells removed close to 4 mg L−1 of U in 24 days. These findings open up promising prospects for sustainable management of U tailings waters based on newly evolved extremotolerants and outline the potential of artificial selection in the improvement of desired features in microalgae by experimental adaptation and selection.